Adubação nitrogenada e potássica na nutrição e produtividade do feijão-caupi sob sistemas de manejo do solo - Belém-Pa - Oliveira, Paulo Custódio Gomes de [UNESP] (2014)
The cowpea (Vigna unguiculata L. Walp ) is one of the most important crops in North and Northeast Brazil, by play key role in the socioeconomic context of low-income families living in these regions . In the state of Pará in Oxisols are predominant area of cultivation of cowpea. These soils are highly weathered, with high acidity, low organic matter, and phosphorus and exchangeable bases and high levels of Al and Fe toxic plants. The objective of this study was to evaluate the effect of nitrogen and potassium fertilization on grain yield, biomass accumulation of shoots and the macronutrient in plant tissue of cowpea. An experiment was conducted under field conditions, from March 2011 to July 2012, in Belém - PA, in a randomized block design in a 4x2 factorial design, with factors four doses of fertilizers ( 100 kg N ha - 1 50 kg K2O ha - 1, the combination of the two dosages and treatment control without fertilization ), two soil management ( conventional tillage and no-tillage ) with four replications . The dry weight of shoots showed significant differences in relation to the studied soil management, fertilization and experiments. The best grain yields were obtained in conventional tillage. Fertilization promoted differentiation for K, Ca and Mg The dry weight of the culture of cowpea remained at high levels.